Non cash payment and demand for real money in Indonesia - Wasiaturrahma Wasiaturrahma; Yuliana Tri Wahyuningtyas; Shochrul Rohmatul Ajija (Universitas Hayam Wuruk Perbanas, 2019)
Non-cash payments in Indonesia are currently developing rapidly. The development of the form of money from just paper money and coins into an electronic money is predicted to have an effect on real money demand, not only in Indonesia. The use of electronic money in Indonesia itself continues to increase especially supported by technological developments. The purpose of this study was to analyse the effect of non-cash payments on real money demand in Indonesia. The method used is Error Correction Model (ECM) using secondary data from 2010 to 2015. The independent variable is the amount of money circulated by Bank Indonesia, and the independent variables used are the value of debit / ATM card transactions, credit cards, and e -money. The results indicate that in the long run credit cards have a significant negative effect on cash circulation in the community, while debit cards have a significant positive effect and affect cash. While in the short term, credit cards and e-money are not significant for cash, and only debit cards only have a significant effect on cash.